Effect of Compaction Pressure and Sawdust Size on Briquette Made from Ulin Wood (Eusideroxylon Zwageri) and Gelam Wood (Melaleuca Cajuputi) to Combustion Characteristics - Pratama, Bagus Harits; Syarief, Akhmad; Saputra, M. Reynaldi Perdana; Azis, Alif Putra (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
In Kalimantan, gelam (Melaleuca cajuputi) Â grows naturally in the swamp forest reaching 40 m with a diameter around 35 cm. Gelam wood is very resistant to acid soil in the swamp forest. Despite of itâ€™s small diameter, gelam wood is very strong. This wood is usually used as the main house, as mold or mall support in casting concrete. Ulin (Eusideroxylon zwageri) is a typical plant of Kalimantan. In this study, the ignition duration, burning speed, and ash weight from briquette made from mixture of ulin and gelam sawdust was investigated. Size of sawdust used for briquette was varied for 40, 50, and 60 mesh while compaction pressure during briquette production was varied for 100, 125 and 150 kg/cm2. The study shows that the highest combustion temperature at 178 oC occurred for briquette with compaction pressure of 150 kg/cm2. Meanwhile, the lowest combustion temperature was obtained in briquette witch compaction pressure of 100 kg/cm2.